Behavior of Discipline Violation And Efforts to Handle It By Guidance And Counseling Teacher - Ramadhani, Fitri Ramadhani; Rahmad, Rahmad; Wei, Zhang; Antti, Thorn (International Journal of Research in Counseling, 2022)
This study aims to examine the behavior of disciplinary violations at SMP N 2 Pulau Punjung and the efforts to handle it by guidance and counseling teachers. Guidance and counseling teachers at SMP N 2 Pulau Punjung made various efforts to deal with this disciplinary violation behavior. These efforts include fostering student attitudes and behavior, outreach to students and parents, developing reward and sanction programs, and collaboration with related parties. The research was conducted using a qualitative approach and case study method. Data obtained through observation, interviews, and document analysis. l Research shows that there are various kinds of disciplinary violations committed by students at SMP N 2 Pulau Punjung, such as arriving late to school, not bringing school equipment, dressing untidy, and being disruptive in class. Factors that influence the behavior of disciplinary violations include the family environment, school environment, and individual student factors.